INFORMÁTICA E HISTORIA ANTIGUA: EL USO DEL PC EN EL ESTUDIO DE LOS TEXTOS CLÁSICOS - Navarro Suárez, Francisco J.; Pérez García, Jesús; Carrión Plaza, José Carlos (Antigüedad y Cristianismo, 1995)
The packet of programs «LEXICO» consists of various programs which: list alphabetically the wordslconcepts (occurrences) and 1) indicates the absolute and relative frecuence of each; 2) in a descending orden te occurrences most used, and 3) a list of the concordances, locating each and noting the context in which they are found. As asterisk indicates when the term occurs more than once in the same line in the original text. (...)